Trelleborgar - vikingatidens drömarkitektur - Wienberg, Jes ; 0009-0006-5623-5580 (META Historiskarkeologisk tidskrift, 2025)
Trelleborg fortresses – the dream architecture of the Viking Age. In 1934, few decades after the idea of the existence of Jomsborg had been critically rejected, a geometric Viking fortress was surprisingly discovered on Zealand, named after the site, a so called Trelleborg fortress. This was followed by the search for more fortresses all over Scandinavia, a search that is still ongoing. Their ramparts and settlement have been published, debated, reconstructed and marked in the landscape. Interpretations and dating have varied over time between different scholars and with several alternative proposals. Since 2023, five Danish Trelleborg sites have been inscribed on the UNESCO World Heritage List. However, only four live up to the normal definition, which leaves out Trelleborgen in Scania, whereas Borgeby also in Scania might be acceptable, however is not investigated sufficiently. The Trelleborg fortresses were icons of the Christian king and has now become national icons for the Viking Age. The Trelleborg fortresses are a questionable dream architecture both then and now attracting widely interest and being a historical-archaeological problem, as the written sources and archaeological evidence doesn’t meet.